Implementastion of Internal Inventory Merchandise Control System - Dita Andhini Setiyowati; Dwi Anggarani; Endah Puspitosarie (Journal of Management Research and Studies, 2023)
Internal control is a security measure to prevent damage, theft or other irregularities. The formulation of the problem in this research is "How is the implementation of the internal control system for merchandise inventory at PT. Sinarmas Distribution Nusantara Malang Branch.” The purpose of this research is to find out how the internal control system for merchandise inventory at PT. Sinarmas Distribution Nusantara Malang Branch. This type of research is descriptive research. The data analysis method used in this research is qualitative analysis. Results of research into PT's internal inventory control. Sinarmas Distribution Nusantara Malang Branch is in accordance with the five components of internal control according to COSO. This shows that internal control over merchandise inventory at PT. Sinarmas Distribution Nusantara Malang Branch is in the very effective category. In order for internal control over inventory to be more effective, companies should be more committed to existing ethics and carrying out work in accordance with predetermined duties and responsibilities.